Associations Between the Density of Oil and Gas Infrastructure and the Incidence, Stage and Outcomes of Solid Tumours: A Population-Based Geographic Analysis - Jost, Evan; Dingley, Brittany; Jost, Casey; Cheung, Winson Y.; Quan, May Lynn; Bouchard-Fortier, Antoine; Kong, Shiying; Xu, Yuan (Frontiers in Oncology, 2021)
Background: We hypothesized that there are geographic areas of increased cancer incidence in Alberta, and that these are associated with high densities of oil and gas(O+G) infrastructure. Our objective was to describe the relationship between O+G infrastructure and incidence of solid tumours on a population level. Methods: We analyzed all patients >=18 years old with urological, breast, upper GI, colorectal, head and neck, hepatobiliary, lung, melanoma, and prostate cancers identified from the Alberta Cancer Registry from 2004-2016. Locations of active and orphan O+G sites were obtained from the Alberta Energy Regulator and Orphan Well Association. Orphan sites have no entity responsible for their maintenance. ArcGIS (ESRI, Toronto, Ontario) was used to calculate the distribution of O+G sites in each census distribution area (DA). Patient residence at diagnosis was defined by postal code. Incidence of cancer per DA was calculated and standardized. Negative binomial regression was done on O+G site density as a categorical variable with cutoffs of 1 and 30 wells/100km2, compared to areas with 0 sites. Results: 125,316 patients were identified in the study timeframe;58,243 (46.5%) were female, mean age 65.6 years. Breast (22%) and prostate (19.8%) cancers were most common. Mortality was 36.5% after a median of 30 months follow up (IQR 8.4 – 68.4). For categorical density of active O+G sites, RR was 1.02 for 1-30 sites/100km2 (95% CI=0.95-1.11) and 1.15 for >30 sites/100km2 (p<0.0001, 95%CI=1.11-1.2). For orphan sites, 1-30 sites RR was 1.25 (p<0.0001, 95%CI=1.16-1.36) and 1.01 (p=0.97, 95%CI=0.7-1.45) for >30 sites. For all O+G sites, RR for 1-30 sites was 1.03 (p=0.4328, 95%CI=0.95-1.11) and 1.15 (p<0.0001, 95%CI=1.11-1.2) for >30 sites. Conclusion: We report a statistically significant correlation between O+G infrastructure density and solid tumour incidence in Alberta. To our knowledge this is the first population-level study to observe that active and orphan O+G sites are associated with increased risk of solid tumours. This finding may inform policy on remediation and cancer prevention.